Advanced hepatocellular carcinoma treated by radiofrequency ablation combined with oncolytic virus and anti-PD-1 antibody therapy: a case report and literature review. Issue 9 (September 2021) - Xie, Anqing; Xia, Feng; Pei, Jun; Sun, Ximing; Song, Zongtao
The development of an effective therapy for advanced hepatocellular carcinoma (HCC) represents an important global concern. In recent years, the combination of multiple treatment methods with immunotherapy has achieved great progress in patients with advanced HCC. Patient survival has been significantly prolonged, but cases of complete response (CR) remain rare. Here, we report two cases in which CR was achieved by radiofrequency ablation combined with an oncolytic virus (recombinant human adenovirus type 5) and anti-programmed cell death protein 1 antibody. Additionally, a literature review is presented to describe similar advancements in this field and explore viable methods for the treatment of advanced HCC.